TELAAH PEMAHAMAN ETIKA PEMASARAN ISLAM PEDAGANG DAN PEMBELI DI PASAR AIR BUNGA KECAMATAN BUAY PEMACA KABUPATEN OKU SELATAN MUARA DUA - Damayanti, Siska; Juniawati, Mutmainah (P3M STIE Mulia Darma Pratama, 2025)
ABSTRACT This study aims to examine the understanding and application of Islamic marketing ethics by traders and buyers at Air Bunga Market in Buay Pemaca District, South OKU Regency. Islamic marketing ethics encompass the values of honesty (shiddiq), trustworthiness (amanah), intelligence (fathanah), communication (tabligh), and consistency (istiqomah), which are rooted in Islamic teachings and emulate the noble character of the Prophet Muhammad (peace be upon him) in business activities. The research method used was qualitative descriptive with a field study approach through interviews, observations, and documentation. The results of the study indicate that most merchants and buyers have a basic understanding of ethical behavior in trading, but have not fully understood the concept of Islamic marketing ethics comprehensively. Ethical practices such as honesty and good service tend to be applied, but there is still inconsistency in maintaining product quality and the information provided to buyers. This study emphasizes the importance of continuous education for business actors so that the application of Islamic ethics in business can be implemented in a comprehensive and consistent manner. Keyword: Traders, Buyer, and Islamic Marketing Ethics